Daenerys Targaryen in George R. R. Martin's A Game of Thrones: Feminist Criticism - Adaninggar Septi Subekti (Faculty of Letters Universitas Balikpapan, 2023)
The study analysed a prominent character in George R. R. Martin's A Game of Thrones, Daenerys Targaryen, through feminist criticism. The study employed qualitative document analysis of the novel where discourse in the forms of characters’ conversations and the author’s narration surrounding Daenerys were interpreted through feminist criticism. The study found seven main themes regarding how Daenerys was portrayed. The first was her obedience to her brother, Viserys. The second was her forced marriage to Khal Drogo for her brother's interest. Thirdly, despite the marriage, Daenerys had an unequal position to Khal Drogo, with her treated as merely an object of sexual pleasure rather than a partner. The next two themes highlight Daenerys' growing courage to defy Viserys and her elevated position among her husband's people after successfully asserting herself in her marriage to Khal Drogo and being pregnant with his boy child. The next theme was her loss of power due to her husband's loss of power due to ill-health. The last highlights her strong conviction against all odds and her self-made rise to power by